The Effectiveness of Acupuncture Therapy in Patient with Hemorrhoid: A Case Report - Fieka Meitaqwatiningarum; Christina Lanny Simadibrata; Irma Nareswari (Journal of Agromedicine and Medical Sciences, 2021)
Background: Hemorrhoid is an anorectal disease due to mechanical disturbances in the anal cushion and hemorrhoid venous plexus blood flow obstruction. Symptoms that often accur are bleeding, pain, prolapse, itching, and mucus discharge. Acupuncture is non-pharmacological therapeutic modalities that has been shown to improve hemorrhoid symptoms. Case: A 37-year-old woman complained of hemorroid lump with pain since last 1 year. Physical examination showed a reddish hemorrhoid prolapse, about 1.5 cm in the posterior anal without bleeding. The pain score with NRS is 4. Acupuncture therapy was performed 3 times a week at acupoints GV20, TE6, LU6, ST25, BL34, ST36, EX-UE2 and BL57. Then given continuous wave electrical stimulation, 4 Hz, 30 minutes retention. After 11 treatments, pain disappeared with NRS 0 and lump was reduced to about 0.5 cm. Conclusion: Acupuncture can improve the symptoms of hemorrhoids, which are seen by the relief of pain and the reduction of lumps. Keywords: Acupuncture, hemorrhoid, hemorrhoid pain, hemorrhoid prolapse